Advancing our understanding of the influence of drug induced changes in the gut microbiome on bone health - Bailey, Stacyann; Fraser, Keith (Frontiers in Endocrinology, 2023)
The gut microbiome has been implicated in a multitude of human diseases, with emerging evidence linking its microbial diversity to osteoporosis. This review article will explore the molecular mechanisms underlying perturbations in the gut microbiome and their influence on osteoporosis incidence in individuals with chronic diseases. The relationship between gut microbiome diversity and bone density is primarily mediated by microbiome-derived metabolites and signaling molecules. Perturbations in the gut microbiome, induced by chronic diseases can alter bacterial diversity and metabolic profiles, leading to changes in gut permeability and systemic release of metabolites. This cascade of events impacts bone mineralization and consequently bone mineral density through immune cell activation. In addition, we will discuss how orally administered medications, including antimicrobial and non-antimicrobial drugs, can exacerbate or, in some cases, treat osteoporosis. Specifically, we will review the mechanisms by which non-antimicrobial drugs disrupt the gut microbiome’s diversity, physiology, and signaling, and how these events influence bone density and osteoporosis incidence. This review aims to provide a comprehensive understanding of the complex interplay between orally administered drugs, the gut microbiome, and osteoporosis, offering new insights into potential therapeutic strategies for preserving bone health.